Carbohydrates designed with different digestion rates modulate gastric emptying response in rats. (2nd October 2020) - Hasek, Like Y.; Phillips, Robert J.; Hayes, Anna M. R.; Kinzig, Kimberly; Zhang, Genyi; Powley, Terry L.; Hamaker, Bruce R.
Abstract: We sought to determine whether design of carbohydrate-based microspheres to have different digestion rates, while retaining the same material properties, could modulate gastric emptying through the ileal brake. Microspheres made to have three slow digestion rates and a rapidly digested starch analogue (maltodextrin) were administrated to rats by gavage and starch contents in the stomach, proximal and distal small intestine, and caecum were measured 2 h post-gavage. A stepwise increase in the amount of starch retained in the stomach was found for microspheres with incrementally slower rates of digestion. Postprandial glycaemic and insulinaemic responses were incrementally lower for the different microspheres than for the rapidly digestible control. A second-meal effect was observed for slowly digestible starch (SDS) microspheres compared to glucose. Thus, dietary slowly digestible carbohydrates were designed to elicit incremental significant changes in gastric emptying, glycaemic and insulinaemic responses, and they may be a means to trigger the ileal brake.